Nanoporous Silicon-Based Direct Hydrochloric Acid Fuel Cells - Dzhafarov, T.D.; AydinYuksel, S. (Journal of Technology Innovations in Renewable Energy, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Fabrication and characterization of Au/Porous silicon/Silicon (Au/PS/Si)-type direct hydrochloric acid fuel cells have been presented in this work. The Au/PS/Si cells were prepared by first creating the nanoporous silicon layer in single-crystalline Si using the anodic etching under illumination and deposition Au catalyst layer onto the porous silicon. The porous silicon filled with hydrochloric acid was developed as a proton conducting membrane. Using HCl:H2O (1.7 M) solution as fuel the open circuit voltage of 0.65 V was obtained and maximum power density of 3.5 mW/cm2 at room temperature was achieved. It is shown that the Au/PS/Si-type direct hydrochloric acid fuel cell with gold catalyst operating at room temperature can be considered as the most promising type of low cost fuel cell for small power-supply units.